Pengaruh Promosi Jabatan dan Disiplin Kerja terhadap Kinerja Karyawan Eiger Letkol Iskandar Palembang - Barik Barik; Hamid Halin; Luis Marnisah (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze the effects of job promotion and work discipline on employees' performance of Eiger Letkol Iskandar Palembang. Data of 30 respondents were collected through interviews and questionnaires. This study applied multiple linear regression to analyze the data. The findings prove that partially, both job promotion and work discipline, each has a significant effect on employees' performance. Likewise, simultaneously promotion and work discipline have a significant and positive effect on employee performance. This insight is beneficial for Eiger Lieutenant Colonel Iskandar Palembang. To improve employees' performance, the manager or store leader should optimize the factors of promotion and work discipline.